Presupuesto por resultados y la calidad del gasto público - Unidad Ejecutora 400 Gerencia Regional de Salud La Libertad: 2015 – 2017 - Aguilar Miguel, Maibi Renee (2019)
ABSTRACT The Budget in the public administration has been treated as a formal act to present the funds that are destined to public institutions that provide various services to the population; However, with the introduction of the Results Budget, this concept is modernized, with the objective of measuring the impact of this management tool on the quality of public spending. The Executing Unit 400 Regional Health Management La Libertad, provides health services in the Provinces of Bolivar and Pataz; the public funds delegated to it are under the justification of the Results Budget; This budget is made up of thirteen budget programs, aimed at improving health services; This is where the hypothesis arises, establishing a close influence of a modern budget management tool and the optimal execution of public funds. The research design was transectional or descriptive transversal, since the data to carry out the study were taken from certain periods; the unit of study was the Executing Unit 400 Regional Health Management for La Libertad during the periods 2015 - 2017 and historical information, reports, budget reports, statistics were analyzed; Translating into tables and figures with results that support the hypothesis. From the results budget and its program structure, the level of compliance of the financial institutions was evaluated. Finally, the influence of the Results Budget on the quality of public expenditure was determined.